The Role of Human Error in Production Process Failures: A Systematic Literature Review - Windy, Windy Wijayanti; Nasution, Harmein; Nurul Huda, Listiani (Jurnal Sistem Teknik Industri, 2025)
Human error One of the most common causes of production failures is human mistake, which can impact product quality, operational efficiency, and workplace safety. This research aims to analyze the role of human error in the production process using various analytical methods found in the literature. This research uses a Systematic Literature Review (SLR) approach to explore the literature related to Human Error in the production process, with the aim of identifying, evaluating, and synthesizing the results of relevant studies. This research shows that 70-90% of quality defects are caused by human error, which impacts quality, increases operational costs, and poses a risk of workplace accidents. Research shows that factors such as lack of training, misunderstanding, as well as an unergonomic work environment, stress, and unclear or complicated SOPs also increase the risk of human error. The use of methods such as CREAM (Cognitive Reliability and Error Analysis Method) is employed to evaluate human reliability and predict Human Error Probability (HEP) in complex cognitive tasks. SHERPA is a method used to identify, predict, and reduce the potential for human error in a system. HEART (Human Error Assessment and Reduction Technique) is a technique designed to estimate the likelihood of human error based on specific working conditions. FMEA (Failure Modes and Effects Analysis) is a systematic method used to identify and analyze potential failures in a process or system.